(untitled) (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Open long bone fractures are frequently complicated by infection and non-union. While external fixation is commonly used for stabilization, it is associated with complications. Recent evidence suggests that antibiotic cement-coated nails (ACCN) provide local antibiotic delivery and stable fixation, to reduce infection and improve outcomes. This study evaluated the effectiveness of ACCN in the management of open long bone fractures. Methods: This ambispective study included 20 patients with Gustilo-Anderson Type II, IIIA, and IIIB open long bone fractures. After thorough debridement, custom-made ACCN were implanted. Patients were monitored using clinical, radiological, and haematological assessments The surgical protocol involved conversion to definitive interlocking intramedullary nailing once haematological markers normalized (at 3 or 6 weeks). If infection persisted, the ACCN was exchanged. Outcomes of infection control and fracture union were assessed at 3 and 6 months. Results: The cohort comprised 17 males (85%) and 3 females (15%) with a mean age of 40.00 ± 11.55 years. Complete infection control was achieved in 16 patients (80%) by 3 weeks and in 2 patients (10%) by 6 weeks. Two patients (10%) required revision ACCN exchange due to persistent infection beyond 6 weeks. No cases of systemic antibiotic toxicity were observed. The majority of patients demonstrated successful fracture union and satisfactory functional outcomes. Conclusion: ACCN are a highly effective therapeutic option for managing open long bone fractures. It providing targeted local infection control and stable fixation, that minimizes pin-site complications, reduces hospitalization, and promotes early rehabilitation. ACCN represents a robust approach to managing complex orthopaedic trauma.